The male novelist and the 'woman question' George Meredith's presentation of his Heroines in The Egoist (1879) and Diana of the Crossways (1885) - Bell, Alan Nigel (Rhodes University, Faculty of Humanities, Department of Literary Studies in English, 2008)
Focusing on four early works, then three from his middle period and three from the 1890s, this dissertation explores Meredith's role as a novelist in the unfolding of a social and literary paradox, namely, that with the death of George Eliot in 1880, the dominant writers of fiction were male, and this remained the case until the advent of Virginia Woolf, while at the same time the woman's movement for emancipation in all spheres of life"”domestic, commercial, professional and political"”was gathering in strength and conviction. None of the late nineteenth-century male novelists"”James, Hardy, Moore and Gissing, as well as Meredith"”was ideologically committed to the feminist cause; in fact the very term 'feminist' did not begin to become current in England until the mid-1890s. But they were all interested in one aspect or another of the 'Woman Question', even if James was ambivalent about female emancipation, and Gissing, on the whole, was somewhat hostile. Of all these novelists, it was Meredith whose work, especially in its last two decades, most copiously reveals a profound sympathy for women and their struggles to realize their desires and ambitions, both inside and outside the home, in a patriarchal world. The dissertation therefore concentrates on his presentation of his heroines in their relationships with the men who, in one way or another, dominate them, and with whom they must negotiate, within the social and sexual conventions of the time, a modus vivendi"”a procedure that will entail, especially in the later work, some transgression of those conventions. Chapter 1 sketches more than two centuries of development in female consciousness of severe social disadvantage, from literary observations in the mid-seventeenth century to the intensifying of political representations in the writings of Mary Wollstonecraft, and the rise of the woman's movement in the course of the Victorian century. The chapter includes an account of the impact on Meredith of John Stuart Mill's The Subjection of Women (1869), and an examination of some of his female friendships by way of illuminating the experiential component of his insights into the 'Woman Question' as reflected in his fiction and letters. His unhappy first marriage is reserved for consideration in Chapter 2, as background to the discussion of The Ordeal of Richard Feverel (1859). This early novel, Meredith's first in the realist mode, is widely accepted as being of high quality, and is given extended treatment, together with briefer accounts of three other early works, The Shaving of Shagpat (1855), Evan Harrington (1861), and Rhoda Fleming (1865), and one from Meredith's middle period, Beauchamp's Career (1876). Two more novels of this period, The Egoist (1879) and Diana of the Crossways (1885), are generally considered to be among his best works, and their heroines are given chapters to themselves (3 and 4). Chapter 5 provides further contextualization for the changing socio-political circumstances of the 1880s and 1890s, with particular reference to that heightening of feminist consciousness represented by the short-lived 'New Woman' phenomenon, to which Diana of the Crossways had been considered by some to be a contribution. Brief discussion of some other 'New Woman' novels of the 80s and 90s follows, giving literary context to the heroines of Meredith's three late candidates in the genre, One of Our Conquerors (1891), Lord Ormont and His Aminta (1894), and The Amazing Marriage (1895). The dissertation concludes with a glance at Meredith's influence on a few early twentieth-century novelists.
Keywords: Meredith, George, 1828-1909 -- Criticism and interpretation; Meredith, George, 1828-1909 -- Egoist; Meredith, George, 1828-1909 -- Diana of the Crossways; English fiction -- 19th century -- History and criticism; English fiction -- Male authors -- History and criticism